Virgindade feminina : uma análise da sua representação no sudoeste do Paraná entre os anos de 1950 a 1980 - Bortoli, Lucas Aguirre de (2016)
This research deals with the difficult subject of virginity and machismo, as well as the questions that arise from these two subjects, considering the society of the south of Paraná from 1950 to 1980, through the investigation of virginity and sexual crimes. Many were the theorists who contributed to the focus of the studies turning to the daily life of people, and the new directions that history has taken, invaded intimacy and today seek to understand the sexual behavior of a given time. Not sexual behavior, for the simple fact of behavior, but addressing this theme and seeking the deep relations of power that determine it, or influences, speeches and representation about sexuality, which influence the attitudes of a large part of society. The history of sexual crimes has become a historical and juridical object, which both historians and jurists thematize. Sexuality must be examined, therefore as a device: it should encompass heterogeneous, discursive and non-discursive elements. The history of ideas, customs and sexual practices allows us to understand the normalization of sexual activities. To exemplify and deepen the analysis on the subject, this work investigated twenty judicial processes framed in Article 217 of the Penal Code of 1940 found in the Forum of the city of Clevelândia / PR, that cover the decades of 1950, 60, 70 and 80. The art . 217 is described as follows in the Criminal Code of 1940: "To seduce the virgin woman, under eighteen and over fourteen, and to have with her carnal conjunction, taking advantage of her inexperience or justifiable confidence: Penalty - seclusion, two To four years.‖Only under these conditions could the crime be classified in Art. 217, otherwise the crime would have another configuration such as rape, sexual harassment, child abuse, or any other. Therefore, we seek the historical rescue of the problem, with a view to overcoming it.